Voices of Teachers: Views on Technology-Based English Learning Resources in Elementary School Settings - Hamid Alwy; Mohamad Fuad Barakwan; Imam Wahyudi Karimullah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The usage of technology-based English learning tools in primary school settings is examined in this study from the perspective of the teachers. In the current digital age, there are numerous tools and platforms available through technology that can improve the educational process. However, several variables, like student involvement levels, teacher preparation, and infrastructural readiness, frequently affect how it is implemented. Several instructors from different primary schools participated in questionnaires and interviews for this study, which determined the advantages and difficulties they encountered when using technological resources. The findings demonstrated that although many educators acknowledged the beneficial potential of technology in enhancing students' English proficiency, they also encountered challenges with restricted devices, internet connectivity, and a lack of training resources. To optimize the efficacy of technology-based English instruction, our findings highlight the significance of continuous professional development for educators and enhancing technology infrastructure in classrooms. It is anticipated that this study will give educators and policymakers valuable information for creating more effective plans for integrating technology into elementary education.